(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The article studied the morphological and morphometric characteristics of the thymus organ of 3, 7, 14 and 21-day-old offspring born from pregnant rats under the influence of chronic stress and compared them with the offspring in the control group. The expected results showed that the thymus of the offspring in the experimental group showed profound and significant morphological changes compared to those in the control group.